Просторова основа міської правосвідомості - Мельничук, Ольга Степанівна; Мельничук, Ольга Степановна; Mel'nichuk, Ol'ga (My University, 2011)
In the article from the points of general theoretical jurisprudence the category of urban legal consciousness is based. The space criteria of legal consciousness classification on urban, peripheral and national is grounded. The structural elements of urban legal consciousness are defined: space (territorial) ideology and space (territorial) psychology.
Мельничук О. С. Просторова основа міської правосвідомості / О. С. Мельничук // Наукові праці Національного університету «Одеська юридична академія». Т. 10 / голов. ред. С. В. Ківалов ; МОНмолодьспорт України, НУ "ОЮА". – Одеса : Юрид. л-ра, 2011. – C. 424-426.
Keywords: міська правосвідомість; міський правовий простір; територіальна правова ідеологія; територіальна правова психологія; городское правосознание; городское правовое пространство; территориальная правовая идеология; территориальная правовая психология; city of justice; Urban legal space; territorial legal ideology; territorial legal psychology